The relationship between caspase-1 related inflammasome expression and serum inflammatory cytokine levels during acute brucellosis - Karaca, Gamze; Karaca, Zeynal Mete; Kayhan, Basak; Bayindir, Yasar; Kayabas, Uner; Toplu, Sibel; Yesilada, Elif (Kare Publ, 2019)
OBJECTIVE: Brucellosis is a zoonotic disease caused by Brucella in domestic and wild animals. It also causes systemic diseases with the involvement of different parts of the human body. An efficient innate immune response is crucial to cure brucellosis with optimum antibiotic treatment. The inflammasomes are innate immune system receptors and sensors that regulate the activation of cysteine-dependent aspartate specific protease-1 (caspase-1) and caspase-1-induced cell death process known as pyroptosis. The aim of the present study was to investigate the expression levels of CASPASE-1 and associated inflammasomes AIM2, NLRP3, and NLRC4 to analyze their relationship with the inflammatory cytokine interleukin (IL)-1 beta, IL-18, and interferon-gamma (IFN-gamma) in peripheral blood samples of patients with acute brucellosis with healthy controls. METHODS: Peripheral blood samples were obtained from 20 healthy volunteers and 20 patients with acute brucellosis. RNA and serum samples were isolated to examine the expression levels of AIM2, NLRP3, NLRC4, and CASPASE-1 by real-time polymerase chain reaction, and IL-1 beta, IL-18, and IFN-gamma were measured by enzyme-linked immunosorbent assay. RESULTS: In the acute brucellosis group, AIM2 and NLRC4 expressions were significantly higher than in healthy volunteers. A significant increase on caspase-1 expression in patients with acute brucellosis was not observed. Serum IL-18 and IFN-gamma levels were significantly higher in patients with acute brucellosis than in healthy controls. CONCLUSION: Caspase-1-related inflammasomes are sufficiently activated to induce the secretion of cytokines, such as IFN-gamma and IL-18, to induce cellular immune response. Caspase-1 activation level should be investigated at different periods of disease in a group with high number of patients to understand the role of pyroptosis and caspase-1 in brucellosis.
Keywords: Acute brucellosis; caspase-1; cytokines; inflammasomes